Human papillomavirus (HPV) genotype distribution in Malaysia: A systematic review - Cassandra Sheau Mei Chee; Shirley Siang Ning Tan; Pei Jye Voon; Yolanda Augustin; Sanjeev Krishna; Nafeesa Mat Ali; Izzati Binti Wan Maharuddin; Xun Ting Tiong; Nur Khairiyah Binti Abdul Rahim; Adam Malik Ismail; Edmund Ui-Hang Sim; Paul CS Divis; et al. (BMC Infectious Diseases)
Abstract Background Human papillomavirus (HPV) is a key etiological factor in cervical cancer in both Malaysia and globally. It continues to pose a significant public health challenge. This systematic review aims to delineate the distribution of HPV genotypes across different demographics in Malaysia to inform targeted prevention strategies. Methods We conducted a systematic review following PRISMA guidelines, analyzing observational studies published from 2000 onward that reported HPV genotypes in cervicovaginal samples from Malaysian women. The review utilized PubMed, SCOPUS, The Cochrane Library, APA PsycNet, and Google Scholar for literature searches, focusing on studies that employed molecular methods for HPV genotyping. Two reviewers independently screened the articles, extracted data, and assessed study quality using the Newcastle-Ottawa Scale (NOS). A descriptive analysis was performed, and findings were synthesized by genotype, region, and ethnicity. Results The review included 22 studies from an initial pool of 2,547 articles, encompassing 44,251 women. These studies reported a HPV prevalence of up to 100% in confirmed cervical cancer cases and in general screenings from 4.5 to 47.7%. A total of 28 different HPV genotypes (high- and low-risk) were identified, with HPV16, HPV18, HPV58, HPV52, and HPV33 being the most prevalent high-risk genotypes. Genotype distributions showed significant variation across different states and ethnic groups within Malaysia, highlighting the diverse nature of HPV-related risks. Conclusions This review provides a detailed snapshot of the HPV genotype distribution in Malaysia, underscoring the necessity for tailored public health interventions that address the regional and ethnic diversity in HPV prevalence. The findings support the need for targeted vaccination programs and enhanced screening measures to effectively combat the high rates of HPV-related (99%) cervical cancer in Malaysia.